Bicycle Level of Service: Proposed Updated Pavement Quality Index. Issue 11 (November 2021) - Huang, Jiayun; Fournier, Nicholas; Skabardonis, Alexander
The Highway Capacity Manual (HCM) employs a simple five-point system to assess the quality of bikeway pavement as part of the comprehensive bicycle level of service (LOS) evaluation. Unfortunately, the ambiguous and rudimentary nature of the existing HCM Pavement Quality Index (PQI) fails to offer an objective review of bikeways across different jurisdictions. In the following analysis, first is an assessment of the PQI and bicycle LOS in the HCM. To demonstrate the impact of the pavement quality rating and the importance of a more standardized evaluation method, a sensitivity analysis is performed. An improved PQI matrix is then proposed based on a comprehensive literature synthesis. The new matrix allows for a more holistic understanding of pavement quality in a three-category framework. The proposed methodology includes specifications for the functionality, structural integrity, and maintenance of bikeways. Within each category, objective thresholds are defined, such as for potholes, cracks, and maintenance routines, to minimize any potential subjectivity.